Peluang E-Commerce Sebagai Platform Bisnis Unggul di Era Digital - Dea Ananda; Qhesya Septian; Windra Windra; Nirmala Nirmala; Suraidah Suraidah (CV. ITTC INDONESIA, 2025)
In the digital era the internet can be utilized in all fields ranging from education, health, government, to business which will make it easier to do everything effectively and efficiently. The internet is currently revolutionizing the way we do business, ranging from small, medium, to large-scale businesses. By utilizing the internet as a business medium, people will get more optimal benefits. This is evident from the statistics of online shopping in the world, Asia, Asia Pacific, and Indonesia itself in the last 5 years. This study will explain how big the opportunity for Indonesian people if they utilize the internet as a business medium.